Pengaruh Kualitas Pelayanan dan Kepuasan Pelanggan terhadap Loyalitas Pelanggan pada Tanjung Decoration - Ainiyatul Mukarromah; Iswati Iswati; Emilia Pranata (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2024)
This study aims to analyze the effect of service quality, perceived value, and customer satisfaction on customer loyalty at Tanjung Decoration. Service quality, perceived value and customer satisfaction are key factors influencing purchase decisions and customer retention in the decoration service industry. However, there has not been much research specifically examining the relationship between these variables in the context of Tanjung Decoration. This research is worth conducting for several reasons. First, Tanjung Decoration is a major player in the fast-growing decoration industry, and an understanding of the factors that influence customer loyalty will help them improve their marketing and service strategies. Second, with a focus on service quality, perceived value, and customer satisfaction, this research will provide valuable insights for managers and practitioners in developing more effective programs to increase customer loyalty. Third, this research will complement the literature on marketing management and consumer behavior by providing a more in-depth understanding of the factors that influence purchasing behavior and customer loyalty in the context of the decoration services industry. By combining appropriate research methodology with a strong theoretical framework, this research is expected to make a significant contribution to the development of knowledge in the field of marketing management and consumer behavior. The results of this study are expected to be a valuable reference source for researchers, practitioners, and other stakeholders interested in understanding and improving customer loyalty in the decoration service industry.